Ultrabroadband superoscillatory lens composed by plasmonic metasurfaces for subdiffraction light focusing. Issue 6 (24th September 2015) - Tang, Dongliang; Wang, Changtao; Zhao, Zeyu; Wang, Yanqin; Pu, Mingbo; Li, Xiong; Gao, Ping; Luo, Xiangang
Abstract : Ultrabroadband optical superoscillatory lens and subdiffraction focusing in the far field are proposed and demonstrated with a plasmonic metasurface. The ultrabroadband feature mainly arises from the dispersionless phase profile across visible and near‐infrared light wavelengths. This method is believed to provide a promising access to broadband far‐field optics beyond the Abbe diffraction limit, such as microscope and telescope systems. Abstract: Conventional optics is diffraction limited due to the cutoff of spatial frequency components, and evanescent waves allow subdiffraction optics at the cost of complex near‐field manipulation. Recently, optical superoscillatory phenomena were employed to realize superresolution lenses in the far field, but suffering from very narrow working wavelength band due to the fragility of the superoscillatory light field. Here, an ultrabroadband superoscillatory lens (UBSOL) is proposed and realized by utilizing the metasurface‐assisted law of refraction and reflection in arrayed nanorectangular apertures with variant orientations. The ultrabroadband feature mainly arises from the nearly dispersionless phase profile of transmitted light through the UBSOL for opposite circulation polarization with respect to the incident light. It is demonstrated in experiments that subdiffraction light focusing behavior holds well with nearly unchanged focal patterns for wavelengths spanning across visible and near‐infrared light. This method is believed to find promising applications in superresolution microscopes or telescopes, high‐density optical data storage, etc.